Faktor-Faktor yang Berhubungan dengan Dukungan Masyarakat Terhadap Program Wingko (Wolbachia ing Kota Semarang) - Mayadilanuari, Aerrosa Murenda; Nurvita, Silvia; Sumantiawan, Dody Indra; Kurniawan, Dhieo (Poltekkes Kemenkes Bandung, 2026)
Background: Dengue fever (DF) remains a persistent public health threat in Semarang City, with 404 reported cases in 2023. To address this issue, the WINGKO Program (Wolbachia ing Kota Semarang) was launched in 2023 as a vector control initiative involving the release of Aedes aegypti mosquitoes inoculated with Wolbachia bacteria. Objective: This study aimed to analyze the factors associated with public support for the WINGKO program. Methods: A cross-sectional study was conducted among 80 residents of RW 2, Meteseh Village, Tembalang District, using a structured questionnaire and purposive sampling technique. Data were analyzed using the Chi-Square test and Pearson correlation to determine the factors influencing community support for the WINGKO Program. Results: The results showed that residents who had lived in Semarang for more than five years were more likely to support the program (OR 3.590, 95% CI 1.247–10.330, p = 0.015). Participants with higher education levels were three times more likely to support the program (OR 3.626, p = 0.006). A history of dengue infection (OR 2.878, p = 0.035) and prior involvement as a Wolbachia Foster Parent (OTA) (OR 3.093, p = 0.044) were also significantly associated with higher program support. In contrast, variables such as gender and household size were not significantly related to support for the program. Conclusion: This research highlights the importance of targeted community engagement strategies that consider educational and experiential factors to strengthen public acceptance.